2019
DOI: 10.3174/ajnr.a5954
|View full text |Cite
|
Sign up to set email alerts
|

Brain DSC MR Perfusion in Children: A Clinical Feasibility Study Using Different Technical Standards of Contrast Administration

Abstract: BACKGROUND AND PURPOSE: Dynamic susceptibility contrast MR perfusion imaging has limited results in children due to difficulties in reproducing technical standards derived from adults. This prospective, multicenter study aimed to determine DSC feasibility and quality in children using custom administration of a standard dose of gadolinium. MATERIALS AND METHODS: Eighty-three consecutive children with brain tumors underwent DSC perfusion with a standard dose of gadobutrol administered by an automated power inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…dynamic-susceptibility contrast perfusion) in children using custom administration of a standard dose of contrast and a reproducible technique as recently suggested. 37 In paediatric stroke, acute downstream involvement of the ipsilateral CST (pre-Wallerian degeneration) predicts poor outcome; 18 Wallerian degeneration as a predictor of poor outcome has been confirmed by the univariate logistic regression analysis in our cohort. Diffusion tensor images represent a more powerful diffusion technique able to identify early pathological changes in the CST after stroke.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…dynamic-susceptibility contrast perfusion) in children using custom administration of a standard dose of contrast and a reproducible technique as recently suggested. 37 In paediatric stroke, acute downstream involvement of the ipsilateral CST (pre-Wallerian degeneration) predicts poor outcome; 18 Wallerian degeneration as a predictor of poor outcome has been confirmed by the univariate logistic regression analysis in our cohort. Diffusion tensor images represent a more powerful diffusion technique able to identify early pathological changes in the CST after stroke.…”
Section: Discussionsupporting
confidence: 58%
“…It is therefore important to plan prospective studies using contrast perfusion techniques (e.g. dynamic‐susceptibility contrast perfusion) in children using custom administration of a standard dose of contrast and a reproducible technique as recently suggested 37 …”
Section: Discussionmentioning
confidence: 99%
“…Other drawbacks of the DSC perfusion method are calcification and hemorrhage-induced susceptibility within the tumor and blood-brain barrier breakdown-related contrast leakage ( 96 ). Despite this, DSC is feasible and has been performed even in young children ( 97 ).…”
Section: Neuroimagingmentioning
confidence: 99%
“…The feasibility of this technique has been derived mostly from brain tumor research, where it has been useful in grading gliomas, differentiating between brain tumor types, and distinguishing tumor from benign lesions 15 . Gaudino et al 16 reported the feasibility, safety, and quality of DSC MR perfusion imaging used in 83 consecutive children with brain malignancy; no cases experienced local or systemic adverse effects, and high-quality CBV maps, signal-intensity time curves, and quantitative evaluations were of diagnostic quality and comparable or superior to adults.…”
Section: Children Are Not Little Adultsmentioning
confidence: 99%
“…There is limited data on DSC perfusion imaging in pediatric stroke, although prior studies, mostly in the brain tumor literature, report that MR perfusion is feasible in children 16 . However, the data for DSC perfusion in acute ischemic pediatric stroke is limited, and it is not yet known whether established adult thresholds defining core infarct and critical hypoperfusion are applicable to children, or whether these parameters can be used to define candicacy for reperfusion therapies in the pediatric population.…”
Section: Perfusion Imaging For Selection Of Pediatric Stroke Patients...mentioning
confidence: 99%